EFFECT OF VARIABILITY OF TEMPERATURE AND RAINFALL ON THE PRODUCTION OF Myrciaria dubia (Kunth) McVaugh, IN UCAYALI, PERU, 2009-2019 - PANDURO-TENAZOA, Nadia Masaya (2023)
Agricultural production is sensitive to climatic factors and the study of their relationships is essential to understand their behavior in the future; for this reason, the objective of this study was to determine the effect of the determining climatic factors on the production of Myrciaria dubia (Kunth) McVaugh, in Ucayali - Peru, 2009-2019; to do this, through the production function, the effect of climatic factors (temperature and rainfall) determining the production of camu-camu in Ucayali was quantified; considering for this, as dimensions of production: yield per hectare, harvested area and the gross value of production for the period 2009 - 2019 and its projection until 2029, using the ordinary least square method (OLS). It was possible to determine that rainfall is the most important climatic factor on yield with 48.79%; and, by 2029, the yield trend is negative, with a reduction of 1.12 t.ha-1. On the other hand, the maximum temperature is the determining climatic factor on the harvested area of camu-camu in 68.82%; by 2029 its projection is positive with an increase of 835.50 ha. Likewise, the maximum temperature is the determining climatic factor on the gross value of camu-camu production at 82.62% and by 2029, its projection will be positive with an increase of 3,546,843.95 PEN